2010
DOI: 10.2355/isijinternational.50.286
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of Secondary Phases in Lean Duplex Stainless Steel 2101 during Isothermal Ageing

Abstract: The DSS ingot was made by standard vacuum melting and casting, which possessed duplex ferritic-austenitic mi- 286© 2010 ISIJ ISIJ International, Vol. 50 (2010) In the present paper, the precipitation behavior of secondary phases in Lean Duplex Stainless Steel (LDX) 2101 had been studied. The alloy has a typical ferritic-austenitic duplex structure after solution treatment. Isothermal ageing treatments were carried out over the temperature range from 700 to 850°C for the period between 2 min and 1 440 min. Cr 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 39 publications
2
11
0
1
Order By: Relevance
“…On the other hand, in Type 32101 of the present study, the value of nanohardness in the α and γ phases was measured to be 3.27-3.78 and 4.14-4.68 GPa, respectively. Fang et al 43) reported that the nanohardness of the α and γ phases were 4.03 GPa and 5.09 GPa, respectively, in Type 32101 after a solid solution treatment at 1 100°C for 30 min. Thus, although the values of our examination were lower than theirs, the γ phase was harder than the α phase in both studies.…”
Section: Texture Formation Of Lean Dss Sheetmentioning
confidence: 99%
“…On the other hand, in Type 32101 of the present study, the value of nanohardness in the α and γ phases was measured to be 3.27-3.78 and 4.14-4.68 GPa, respectively. Fang et al 43) reported that the nanohardness of the α and γ phases were 4.03 GPa and 5.09 GPa, respectively, in Type 32101 after a solid solution treatment at 1 100°C for 30 min. Thus, although the values of our examination were lower than theirs, the γ phase was harder than the α phase in both studies.…”
Section: Texture Formation Of Lean Dss Sheetmentioning
confidence: 99%
“…In addition, the experimental results also reveal that the ferrite phase percentage decreases in an opposite tendency to sigma phase and in a similar magnitude. This phenomenon is associated to the decomposition that ferrite experiments to form sigma phase and secondary austenite [16,44,45]. The objective of different percentages of sigma phase precipitated is to analyze the behavior of the phases in the first stages of sigma phase nucleation in α-α as well as α-ɣ boundaries, and in the subsequent stage, where the sigma phase grows towards the ferrite phase.…”
Section: Qualitative and Quantitative Analysis Of The Phasesmentioning
confidence: 99%
“…The fracture toughness, 3) precipitation of nitrides with heat treatment, 4) and improvement of mechanical properties using stressinduced martensitic transformation of the γ phase 5,6) have been reported for lean duplex stainless steels. Herrera et al 5) investigated duplex stainless steel with α and γ volume fractions of 37% and 63%, respectively, from a Fe-19.9Cr-0.42Ni-0.16N-4.79Mn-0.11C-0.46Cu-0.35Si steel.…”
Section: Introductionmentioning
confidence: 99%